PROGRAMMABLE LOGIC CONTROL - TOGAR TIMOTEUS GULTOM (LP2MTBM MAKARIOZ, 2020)
The development of science and technology (IPTEK) today is very rapid, especially in the field of electronic technology so itgreatly affects human life to go further (modernization), pragmatic thinking and simple. Where practical and technologicalsupporting facilities are needed. This can be realized by the use of all automatic equipment that reduces the role of humansas a subject of work that has been widely found. To meet the automation needs of practical and accurate control equipmentWearable control tools such as microcontroller based control tools, automatic switches, and programmable logic control(PLC).